A multi-state analysis on the effect of deprivation and race on PICU admission and mortality in children receiving Medicaid in United States (2007-2014) - Hannah K. Mitchell; Joshua Radack; Molly Passarella; Scott A. Lorch; Nadir Yehya (BMC, 2024)
Abstract Introduction In the United States (US), racial and socioeconomic disparities have been implicated in pediatric intensive care unit (PICU) admissions and outcomes, with higher rates of critical illness in more deprived areas. The degree to which this persists despite insurance coverage is unknown. We investigated whether disparities exist in PICU admission and mortality according to socioeconomic position and race in children receiving Medicaid. Methods Using Medicaid data from 2007-2014 from 23 US states, we tested the association between area level deprivation and race on PICU admission (among hospitalized children) and mortality (among PICU admissions). Race was categorized as Black, White, other and missing. Patient-level ZIP Code was used to generate a multicomponent variable describing area-level social vulnerability index (SVI). Race and SVI were simultaneously tested for associations with PICU admission and mortality. Results The cohort contained 8,914,347 children (23·0% Black). There was no clear trend in odds of PICU admission by SVI; however, children residing in the most vulnerable quartile had increased PICU mortality (aOR 1·12 (95%CI 1·04-1·20; p = 0·0021). Black children had higher odds of PICU admission (aOR 1·04; 95% CI 1·03-1·05; p < 0·0001) and higher mortality (aOR 1·09; 95% CI 1·02-1·16; p = 0·0109) relative to White children. Substantial state-level variation was apparent, with the odds of mortality in Black children varying from 0·62 to 1·8. Conclusion In a Medicaid cohort from 2007-2014, children with greater socioeconomic vulnerability had increased odds of PICU mortality. Black children were at increased risk of PICU admission and mortality, with substantial state-level variation. Our work highlights the persistence of sociodemographic disparities in outcomes even among insured children.